ANALYSIS OF GEOTEXTILE EMBANKMENT BY ANSYS (Journal of Engineering, 2011)
The major objectives of this research are to analyze the behavior of road embankmentsreinforced with geotextiles constructed on soft soil and describe the finite element analysis by usingANSYS program ver. (5.4). The ANSYS finite element program helps in analyzing the stability ofgeo- structure (embankment) in varied application of geotextiles reinforcement to enhance the bestdesign for embankment.The results of analysis indicate that one of the primary function of geotextiles reinforcement was toreduce the horizontal displacement significantly. With the inclusions of reinforcement, the horizontaldisplacement reduced by about (81%), while the vertical displacement reduced by (32%). The effectof geotextiles stiffness modulus on horizontal and displacement is quite significant even a very highmodulus of geotextile will have relatively little effect on vertical displacement. Also it is observedfrom the obtained results that the maximum displacement occurred at the toe of embankment for bothhorizontal and vertical movement, then decrease gradually to a negligible value for the layerreinforced case. Also the reinforcement reduces the shear stress developed in the foundation soil.